Maze Of Faith : Shalat yang Sempurna - Muzzammil Rahmat Edi (JASTEN (Jurnal Aplikasi Sains Teknologi Nasional), 2024)
The development of the gaming industry demands developers to create more immersive playing experiences. In this context, the use of Finite State Machine (FSM) has become a popular and effective solution for managing storyline progression and structured character development. This article discusses the basic concepts of FSM and illustrates its implementation in the game "Maze of Faith: Perfect Prayer" as a means of education and entertainment. The application of FSM in this game aims to enhance gameplay dynamics and provide a clear structure to the player's journey. The article elaborates on the fundamental FSM concepts applied in the game, highlighting how FSM usage can improve the quality of the playing experience for gamers. Through an analysis of FSM implementation in this game, the article provides a deeper understanding of how the FSM framework can be utilized to control storyline progression, character behavior, and overall gameplay dynamics. The implementation of FSM in "Maze of Faith: Perfect Prayer" has a positive impact on creating a well-structured, dynamic, and relevant playing experience aligned with modern player expectations.